The Influence of Surveillance, The Discipline of Work, Work Environment Toward Performance Employee Of The Vanname Shrimp Farm CV. Alam Citra Sarana Intam - Fiqri, Muhammad; Mayangsari, Andina (Jurnal Manajemen Agribisnis dan Agroindustri, 2025)
The most important part in realizing a company so that the activities carried out can be organized and appropriate are its human resources. Employees in the company must have the ability and knowledge so that the company runs optimally. Aspects such as surveillance , discipline, and work environment can affect the quality of employee performance. CV. Alam Citra Sarana Intam has a total of 30 employee in all fields. Both primary and secondary data were used in this study with SPSS 26.0 for windows software as a tool in analyzing data using multiple regression. The results obtained from this study are: (1) Simultaneously the independent variables namely surveillance (X1), work discipline (X2), work environment (X3) influence the dependent variable namely employee performance (Y). (2) The variable of surveillance (X1) partially has no effect but the variable of work discipline (X2) and work environment (X3) has an influence on employee performance (Y). (3) The variable that has the dominant influence is work discipline (X2).